MENINGKATKAN CINTA, BANGGA, & PAHAM RUPIAH MELALUI SOSIALISASI DAN SIMULASI TRANSAKSI SISWA SD DESA KUTAMBARU - Devi Herawati; Albina Humaira Manurung; Rezza Pramudipa; Atikah Atikah (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Efforts to improve financial literacy and foster pride in the Rupiah were carried out through the integration of the “Love, Proud, Understand (CBP) Rupiah” campaign with practical transaction simulations for elementary school students (grades 4 to 6) in Kutambaru. As a symbol of national sovereignty, the Rupiah requires early understanding to prevent improper treatment and to enhance financial literacy. The methods used included interactive lectures and experiential learning to deliver materials such as the introduction to the Rupiah, its meaning and role, and its security features, followed by transaction simulations using a menu booklet to test practical skills. The results showed high student enthusiasm during the socialization activities, with students demonstrating confidence in identifying the security features of the Rupiah. In the transaction simulation practice, approximately 43% of students completed the tasks perfectly, while the remaining 57% made minor errors related to calculation and accuracy. This approach proved effective in developing both theoretical and practical understanding, although further reinforcement is needed to improve accuracy for optimal results